Association of sleep symptoms with mood and vestibular subtypes following sport-related concussion. Issue 3 (3rd July 2022) - Brustman, Kelly; Eagle, Shawn R.; Mucha, Anne; Trbovich, Alicia; Collins, Michael W.; Kontos, Anthony P.
Abstract: Sport-related concussion (SRC) is a heterogenous injury with diverse symptoms and impairments that can be aggregated into clinical subtypes (cognitive, headache/migraine, vestibular, ocular-motor, anxiety/mood). Sleep disruption has been defined as potential exacerbating conditions that may accompany the five clinical subtypes. The authors sought to better characterize the role of impaired sleep in each clinical subtype and to identify other risk factors for sleep impairment after SRC. 281 patients (15.3 ± 2.1 years) aged 10–22 years within 21 days of SRC completed the Post-Concussion Symptom Scale (PCSS), the Vestibular/Ocular Motor Screening (VOMS), and a clinical assessment to identify clinical subtype. Subjects were then divided into HIGH (≥7; n  = 82) and LOW (≤3; n  = 132) sleep symptom groups for comparison. HIGH participants had greater proportions of females ( p  < 0.001), history of psychiatric disorder ( p  < 0.001); total PCSS ( p  < 0.001); and impairment on all VOMS items ( p  < 0.001). HIGH participants were associated with mood/anxiety ( p  < 0.001), vestibular ( p  = 0.003) and ocular ( p  = 0.03) subtypes. Results of a logistic regression (LR) model with adjusted odds ratios (OR) to predict HIGH sleep symptoms supported anxiety/mood profile (OR = 2.98), vestibular profile (OR = 2.81), psychiatric history (OR = 4.99), and history of motion sickness (OR = 2.13) as significant predictors. Prescribing behavioral and sleep interventions may improve outcomes in cases where these factors co-occur.